PHILOSOPHY OF ACTION W. JAMES - Льовкіна, О. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The analysis of philosophy of action of pragmatism is offered in the article. Attention of author is concentrated on the features of the methodological program of pragmatism. Speech goes about its antispeculative orientation, walking away from the classic method of rationality of cognition, aspiring to religiously-moral definition of purpose of activity.